Evaluating the quality of life of patients with extrapyramidal complications in the rehabilitation period after a stroke after complex treatment - Ovodiuk, N. (Journal of Education, Health and Sport, 2018)
Introduction. Among the vascular diseases of the brain, the most widespread and grave consequence is a cerebral infarction (CI) which in 78% of cases leads to disability. In a significant proportion of patients who suffered an ischemic stroke there is a complicated motor defect that differs in character and degree and causes postural abnormalities, disorders of movements coordination and is associated with the phenomenon of metabolic diashysis.Materials and methods of research. To study, we selected a group of patients (civil servants) who suffered an ischemic stroke of working age - 24 patients aged 40 to 60 years with varying degree of motor neurological, emotional-will and mental deficiency for at least 6 months after CI, and those who returned to work. Patients selected from the study group showed varying degree of extrapyramidal disorders. All patients were evaluated for the quality of life by standardized questionnaire SF-36.Results and discussion. As a result of the study it was found that a number of neurological syndromes and/or complexes of syndroms occurred in patients with dyscirculatory encephalopathy of the working age who suffered an ischemic stroke against a background of arterial hypertension, namely: vestibular ataxic syndrome (62%), cephalgic (72%), cerebral asthenia (88%), amnestic syndrome (82%) and anxiety-depressive syndrome (66%). In women, cerebral asthenia (88.2%), amnestic (76.5%) and anxiety-depressive (82.2%) syndromes were prevalent, cerebral asthenia (90.9%), amnestic syndrome (84.8%), cephalgic ( 78.8%) and anxiety-depressive (78.8%) syndromes were prevalent in men.Conclusions. Thus, in the course of the study we have found that in order to cure the complications of extrapyramidal disorders after a stroke, it is proposed to involve neurological patients in physiotherapy and reflexotherapy more widely. It is recommended to use standardized quality of life questionnaires to assess the quality of life of patients who have suffered a stroke.